A Five‐Year Retrospective Analysis Comparing Morbidity and Mortality Outcomes of Previous Myomectomy Surgical Delivery, and Elective Repeat Caesarean Section - Michelle Bailey; Marvin Reid; Vernon DaCosta (Reproductive, Female and Child Health)
ABSTRACT Objectives To determine the differences in maternal and neonatal morbidity between three groups of women, Group 1, women with a previous myomectomy, (n = 69), Group 2, women who had an elective caesarean section (n = 92), and Group 3, women who have had a previous myomectomy and previous caesarean section (n = 33), who were all delivered by a current caesarean section. Methods One hundred and ninety‐four women were enrolled consecutively from the labour ward booklist at the University Hospital, during 2015–2020. Women who had a stillbirth or delivered vaginally were excluded from this study. Demographic data and maternal and foetal outcomes were collected from eligible patient records. Postpartum haemorrhage (PPH) at caesarean section was defined as a blood loss of 1000 mL or higher. Results The mean (SD) age of the women was 35.5(4.6) years. The prevalence of post‐partum haemorrhage in the sample was 17.9%, with a significant difference in blood loss between the groups adjusting for surgical complications, parity, adhesions and mode of anaesthetic delivery. Specifically, women in Group 2 had an 80% lower risk for PPH when compared with Group 1, and there was no significant difference in risk between Group 3 and Group 1. There was no difference in neonatal morbidity between the groups. Conclusion There was overall a low maternal and neonatal morbidity associated with women who have had a previous myomectomy, a previous caesarean section or both. Notwithstanding, PPH is a concern and therefore, strategies to mitigate PPH are required.